Upaya Pencegahan Perkawinan Anak Pada Masyarakat Penerima Program Keluarga Harapan (PKH) di Sonobabar Grobogan - Maskur, Ali; Rismana, Daud; Adilla, Arina Hukmu; Chamami, M Rikza (JRCE (Journal of Research on Community Engagement), 2024)
The focus of dedication to this community is to reduce the number of child marriages in the recipient community of Program Keluarga Harapan (PKH) in Sonobabar Dusun Gedangan Grobogan. The PKH programme by the Ministry of Social Affairs of the Republic of Indonesia aims to help the economy to eradicate poverty. But the rise in the number of child marriages in poor areas increases the burden on society. Economic, social, educational and health disruption is an acute problem in the region. Participary Action Research (PAR) approach is chosen by servants to find problems, discern and find solutions together with the community. The result of this dedication is 1. The importance of socializing about the dangers of child marriage for young brides. Lack of preparedness in terms of economics, reproductive health and mental health because it is not ready to go through households and take care of children will be a problem in the future. It is necessary to enhance cooperation and support to promote the economy and legal awareness of the dangers of child marriage between the facilitator of the PKH of the Ministry of Social Affairs, the religious advocate of the Office of Religious Affairs (KUA) of the ministry of Religion, Bidan Village and the village government in Dusun Sonobabar Gedangan Grobogan.